Developing Electronic Module Assisted by Professional Flip PDF Application in Kepewaraan Course - Wirahyuni, Kadek; Martha, I Nengah; Suandi, I Nengah (PT. Riset Press International, 2023)
This study aims to 1) analyze the characteristics of the e-module in the Kepewaraan course at the Universitas Pendidikan Ganesha and 2) analyze the quality of the e- in the Kepewaraan course at the Universitas Pendidikan Ganesha. This study applied the ADDIE model, namely analysis, design, development, implementation, and evaluation. The subjects of the study were; 1) a learning content expert, media expert, learning design expert, and language expert; 2) three students in the fifth semester, and 3) six people in small groups. Data collection methods were observation, interviews, and questionnaires. The research results show that; 1) the characteristics of this e-module have been developed through several stages, namely analysis, design, development, implementation, and evaluation; 2) the score from content experts is categorized into good qualifications (96.47%), the score of learning design experts is categorized into very good qualifications (93.33%), the score of learning media experts is categorized into very good qualifications (97.5 %), the score of individual trials is classified into very good qualifications (95.53%), and the score of small group trials is categorized into very good qualifications (95.53%). Based on the results of the experts, it can be concluded that the e-module in the Kepewaraan course is feasible to apply.